Bacillus cereus in Dairy Products and Production Plants - Erica Tirloni; Simone Stella; Francesco Celandroni; Diletta Mazzantini; Cristian Bernardi; Emilia Ghelardi (Foods, 2022)
Spore-forming Bacillus cereus is a common contaminant of dairy products. As the microorganism is widespread in the environment, it can contaminate milk at the time of milking, but it can also reach the dairy products in each phase of production, storage and ripening. Milk pasteurization treatment is not effective in reducing contamination and can instead act as an activator of spore germination, and a potential associated risk still exists with the consumption of some processed foods. Prevalences and concentrations of B. cereus in milk and dairy products are extremely variable worldwide: in pasteurized milk, prevalences from 2% to 65.3% were reported, with concentrations of up to 3 × 105 cfu/g, whereas prevalences in cheeses ranged from 0 to 95%, with concentrations of up to 4.2 × 106 cfu/g. Bacillus cereus is also well known to produce biofilms, a serious concern for the dairy industry, with up to 90% of spores that are resistant to cleaning and are easily transferred. As the contamination of raw materials is not completely avoidable, and the application of decontamination treatments is only possible for some ingredients and is limited by both commercial and regulatory reasons, it is clear that the correct application of hygienic procedures is extremely important in order to avoid and manage the circulation of B. cereus along the dairy supply chain. Future developments in interventions must consider the synergic application of different mild technologies to prevent biofilm formation and to remove or inactivate the microorganism on the equipment.